The effectiveness of local wisdom-based static fluid modules in the wetlands environment - Wati, Mustika; Misbah, Misbah; Haryandi, Surya; Dewantara, Dewi (Momentum: Physics Education Journal, 2020)
This study aims to describe the effectiveness of static fluid module based on local wisdom in the wetlands environment. This study is a research and development study and uses the 4D model modified. The effectiveness of the module is measured using a learning outcome test. The subjects of this study were sixty grade XI students from two public high schools in Banjarmasin city. The result of the analysis showed that the effectiveness of teaching materials have a medium category. The result indicates that the static fluid module based on local wisdom in the wetland environment is effective so that they can be used in the learning process in the classroom, at the high school level.